Investigating the Bajau and Batiq indigenous culture in an attempt to produce new series of art works / Sima Nader Tehrani - Tehrani, Sima Nader (2015)
After engaging in research and practicing studio painting to gain experience in reinterpreting culture, I sought a way to integrate the ethnographical methodology into my artwork. I decided to express my experiences with the Bajau (Sabah) and Batiq (Pahang) tribes in my new body of artwork. As Malaysia is a multiracial country with a multitude of ethnic groups, I have chosen to study and investigate two groups that have been investigated by only a handful of artists thus far. Being natives, most of them display a rather simple and naive disposition. Their life is reminiscent of the peace and beauty of olden days, which I find so inspiring. This research is significant to me because it provides me with the opportunity to experience and to reinterpret the cultural complexities of the indigenous tribes of Bajau (in Sabah) and Batiq (in Pahang) in a series of artworks. Using symbols such as abstract figuration to create visual narratives through formal elements such as color and composition will be the objectives of this research. One of the ways to effectively conduct this research is to observe directly and artistically the lifestyles of these two selected Malaysian tribes. Creating artworks is the main part of this research and it will be done in the studio. To facilitate the manifestation of the idea in creating my artwork, visiting museums and art galleries was a starting point. In my process of creating my artwork, I was influenced by Picasso and how he was inspired by the African Mask. Gauguin's narration of Tahitian life also inspired me significantly. I also share similar experience with American artist Robert Rauschenberg when he visited Malaysia; the work of Chuah Thean Teng who showed the role of women in life, while Calvin Chua inspired me with his travels to meet indigenous people. Zulkifli Buyong's naive style of paintings that depict Malaysian urban culture is part of my references. The analysis of my work relies greatly on Roland Barthes and Ferdinand de Saussure's mode of interpretation. Both discussed at length the issue of representation and meaning, signified and signifier. As a result, a new series of artworks is produced and exhibited alongside a supporting desideration of an exegesis. Exhibiting the artworks is the ultimate aim of this research that will add to new directions in the researcher's artistic endeavors.